2017
DOI: 10.1093/biolre/iox088
|View full text |Cite
|
Sign up to set email alerts
|

Seipin deficiency leads to defective parturition in mice†

Abstract: Seipin is an integral endoplasmic reticulum membrane protein encoded by Berardinelli-Seip congenital lipodystrophy type 2 (BSCL2/Bscl2) gene. Seipin deficiency results in lipodystrophy, diabetes, muscle hypertrophy, and male infertility in both human and mouse. Seipin function in female reproduction is unknown. Bscl2 −/− dams had normal embryo implantation and body weight gain during pregnancy but reduced delivery rates from 2nd to 4th pregnancies and reduced numbers of pups delivered from 1st to 4th pregnanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Bscl2 −/− females have impaired lactation Bscl2 −/− females had comparable mating activity with age-matched control females when they were mated with WT (Bscl2 +/+ ) stud males. The average numbers and sizes of implantation sites examined on gestation day 13.5 were comparable between control and Bscl2 −/− females [23], indicating no obvious defects in early pregnancy events, such as ovulation, fertilization, embryo development, embryo implantation, and placental development in Bscl2 −/− dams. However, among the 22 litters delivered by Bscl2 −/− females (2-4 months old, mated with WT stud males), 13 of them had 1-10 pups per litter at birth (PND1) but all live pups at birth in these 13 litters were dead by PND5 due to lack of milk in their stomachs ( Figure 1A).…”
Section: Resultsmentioning
confidence: 81%
“…Bscl2 −/− females have impaired lactation Bscl2 −/− females had comparable mating activity with age-matched control females when they were mated with WT (Bscl2 +/+ ) stud males. The average numbers and sizes of implantation sites examined on gestation day 13.5 were comparable between control and Bscl2 −/− females [23], indicating no obvious defects in early pregnancy events, such as ovulation, fertilization, embryo development, embryo implantation, and placental development in Bscl2 −/− dams. However, among the 22 litters delivered by Bscl2 −/− females (2-4 months old, mated with WT stud males), 13 of them had 1-10 pups per litter at birth (PND1) but all live pups at birth in these 13 litters were dead by PND5 due to lack of milk in their stomachs ( Figure 1A).…”
Section: Resultsmentioning
confidence: 81%
“…The middle three sections with the largest areas were selected for area quantification. The total area of each placental section and the areas of labyrinth layer, junctional zone, and decidua, which were outlined manually and quantified using Image J (National Institutes of Health, Bethesda, MD, USA) [35][36][37][38]. The average of each area from three sections in the same placenta was counted as one data point for statistical analysis.…”
Section: Histology and Quantification Of Placental Layersmentioning
confidence: 99%
“…Cross sections (10 μm) of the middle part of frozen placentas from 0 ppm and 40 ppm ZEAtreated groups were collected on the same slides for immunofluorescence. The sections were fixed in 4% paraformaldehyde for 15 min, and blocked with 3% hydrogen peroxide in methanol for 10 min at 25°C, and 10% goat serum in 1x phosphate buffered saline (PBS) for 1 hour at 25°C, incubated with rabbit anti-proliferating cell nuclear antigen (PCNA (D3H8P)1:250, 13110XP, Cell Signaling Technology, Danvers, MA, USA) overnight [35,38,39]. On the second day, the slides were incubated with goat anti-rabbit secondary antibody (Alexa Fluor 288, 1:200, A-11034, ThermoFisher, Rockford, IL, USA).…”
Section: Proliferating Cell Nuclear Antigen (Pcna) Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Seipin deficiency has been reported to aggravate I/R-induced cerebral damage ( 26 ). Seipin mutations at glycosylation sites result in the activation of autophagy ( 27 , 28 ). Our recent study reported that neuronal Seipin deletion reduces autophagosome formation to cause hyperphosphorylation and aggregation of tau protein through reduced inhibition of peroxisome proliferator-activated receptor γ in Akt/mTOR signaling ( 29 ).…”
Section: Introductionmentioning
confidence: 99%